2019
DOI: 10.1088/1757-899x/670/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties evaluation of nonwoven industrial cotton waste produced by needle punching method

Abstract: This paper describes the fabrication method and mechanical characterization of nonwoven fabrics from industrial fabric wastes by different machine variables. Cotton waste fibres underwent the mechanical recycling methods, needle punching process and worked into a continuous web of nonwoven fabrics. The measurement method of full factorial design of experiment was implemented in this study as a systematic and efficient way to distinguish between the interaction of more than one factor which are the fibre feeder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Cotton fibres that are removed during ginning and textile manufacturing processes are waste cotton. A study performed by Latifi et al (2019) showed the production of a cotton waste nonwoven web using the nonwoven needle-punching method [137]. The results showed that processing factors such as fibre feeder speed and number of stacking layers have a notable impact on the mechanical properties of the fabrics.…”
Section: Waste Cottonmentioning
confidence: 99%
“…Cotton fibres that are removed during ginning and textile manufacturing processes are waste cotton. A study performed by Latifi et al (2019) showed the production of a cotton waste nonwoven web using the nonwoven needle-punching method [137]. The results showed that processing factors such as fibre feeder speed and number of stacking layers have a notable impact on the mechanical properties of the fabrics.…”
Section: Waste Cottonmentioning
confidence: 99%
“…More research is needed because confounding experimental variables include not only the dyes but also the prior history of chemical (e.g., alkaline) treatments to the cotton matrix [62], which may affect interactions between cotton and the matrix. In addition to composites, waste cotton fibers can also be incorporated in nonwovens [79], acoustic insulation [80] and building materials [81]. For example, Husain et al, used a needle punching method to convert cotton fabric waste into nonwovens [79].…”
Section: Cotton Mechanical Recyclingmentioning
confidence: 99%
“…In addition to composites, waste cotton fibers can also be incorporated in nonwovens [79], acoustic insulation [80] and building materials [81]. For example, Husain et al, used a needle punching method to convert cotton fabric waste into nonwovens [79]. Hawley's description of textile recycling systems offers additional descriptions of processes and applications for mechanically recycled textile waste, including cotton waste, such as paper pulp and wiping cloths [82].…”
Section: Cotton Mechanical Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-sustainable disposal practices provoke efforts to recycle textile wastes and bring renewed value to their components (Pang et Cotton, as the most popular natural ber, occupies the second largest market share (24%) in textiles (Cotton Inc.; Textile Exchange 2021), yet this also means that tons of cotton waste are produced every year. Various mechanical and chemical recycling methods have been developed to improve cotton textile reuse (de Silva and Byrne 2017; Serra et al 2018;Husain et al 2019;Johnson et al 2020; Damayanti et al 2021). In mechanical recycling, cotton textile wastes are cut, shredded and combed to recover intact staple length bers for re-spinning.…”
Section: Introductionmentioning
confidence: 99%